Fishes of the Sea of Oman - Eagderi, Soheil; Mouludi-Saleh, Atta; Fricke, Ronald; Alavi-Yeganeh, Mohammad Sadegh; Mosavi-Sabet, Hamed; Cicek, Erdogan (Iranian Journal of Ichthyology, 2026)
This study assembled a comprehensive list of fish species for the Oman Sea (Gulf of Oman). The areas considered were focused on the northeast coast of Oman, the short eastern coast of the UAE, the southern coast of Iran, and the westernmost part of the Baluchistan/Pakistan coast. Our findings suggested the presence of 1047 species in 2 classes, 39 orders, 164 families, and 526 genera. Class Actinopteri had 647 species (90.44% of total species), and 100 (9.56%) species belong to Elasmobranchii. A total of 86 species were recorded for the first time from the Oman Sea in this study. The highest species number was recorded for the order and family of Acanthuriformes (225 species) and Carangidae (57 species), respectively. Using IUCN categories, the conservation statuses of fishes in the Oman Sea are: 114 Not Evaluated, 77 Data Deficient, 747 species of Least Concern, 19 Near Threatened, 43 Vulnerable, 26 Endangered, and 21 in Critically Endangered.
Keywords: Faune -- Oman

الصقر الأسود في عمان (دراسة عن الصقور العمانية) عام 1978 - Hartmut, Walter (وزارة التراث القومي والثقافة, 1984)
Keywords: Faune -- Oman

The Mammal Fauna of Oman = الحيوانات البرية في عمان - Harrison, David L. (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Faune -- Oman

al-Salāḥif al-Baḥriyya fī Salṭanat ʿUmān - Sālim, Rūd; Sālim, Sūzān (The Omani Historical Society, 1991)
Keywords: Faune -- Oman

A new list of the birds of Masira island, Sultanate of Oman - Rogers, T.D. (The Oman Bird Record Committee, 1988)
Keywords: Faune -- Oman